2007
DOI: 10.1016/j.elecom.2006.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Template electrosynthesis of La(OH)3 and Nd(OH)3 nanowires using porous anodic alumina membranes

Abstract: High quality arrays of Ln(OH) 3 (Ln = La, Nd) nanowires have been successfully fabricated for the first time by an electrochemical process using anodic alumina membrane templates. A physico-chemical characterisation of electrodeposited hydroxides has been carried out by different techniques (XRD, SEM and EDX). The results show that the synthesized nanostructures are crystalline, dense, continuous, well aligned, and with high aspect ratio, suggesting further development of possible applications in the lanthanid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…Oxide can be directly produced via electrogeneration of base from properly selected organic solvent or indirectly by thermal treating the corresponding hydroxide. This technique has been recently adapted as a soft electrochemical route to the preparation of nanotubes/nanowires metal hydroxides and/or oxides through the employment of a template [5][6][7][8][9]. The deposition of metal hydroxides involves two steps at the cathode/electrolyte interface: the cathodic generation of hydroxyl ions and the chemical precipitation of the hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide can be directly produced via electrogeneration of base from properly selected organic solvent or indirectly by thermal treating the corresponding hydroxide. This technique has been recently adapted as a soft electrochemical route to the preparation of nanotubes/nanowires metal hydroxides and/or oxides through the employment of a template [5][6][7][8][9]. The deposition of metal hydroxides involves two steps at the cathode/electrolyte interface: the cathodic generation of hydroxyl ions and the chemical precipitation of the hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Cd, the reduction of Cd 2+ ions to metallic Cd has a standard equilibrium potential higher with respect to the other metals whose hydroxides have been precipitated into AAMs [7,9,10]. Thus, the reduction process involving Cd 2+ can completely suppress the OH -generation from H 2 O reduction, as reported in…”
Section: Introductionmentioning
confidence: 63%
“…Recently, template-assisted electrochemical synthesis has been shown to be a versatile, simple and low temperature approach for the preparation of metals oxide/hydroxide nanostructures [6][7][8][9][10]. The deposition usually occurs through a mechanism of electroprecipitation, according to which base is generated at the cathode/ electrolyte interface, where the hydroxide reaches its solubility product owing to the local increase of pH [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, lanthanum hydroxide, La(OH) 3 , has been electrochemically deposited. Bocchetta et al first showed that it was possible to obtain La(OH) 3 from a solution of lanthanum nitrate using galvanostatic deposition at a cathodic current of 1 mA/cm 2 [40]. They obtained nanowires on an Al substrate, and the authors proposed that deposition occurred through a base generation mechanism.…”
Section: Electrochemical Synthesis Of Lanthanum Oxide (La 2 O 3 )mentioning
confidence: 99%
“…There are only a few papers reporting the attempt to electrodeposit lanthanum oxides from aqueous solutions [39][40][41][42]. In practice, La 2 O 3 has not been deposited directly using electrodeposition.…”
Section: Electrochemical Synthesis Of Lanthanum Oxide (La 2 O 3 )mentioning
confidence: 99%